2020
DOI: 10.1016/j.postharvbio.2019.111104
|View full text |Cite
|
Sign up to set email alerts
|

Apparent respiratory quotient observed in headspace of static respirometers underestimates cellular respiratory quotient of pear fruit

Abstract: A three-compartment non-equilibrium gas transport model of 'Conference' pear fruit under controlled atmosphere (CA) storage was developed. The model fruit tissue consists of cells, in which the concentrations of respiratory gasses can show gradients, and intercellular space, in which gasses are uniformly distributed. Non-equilibrium of gas concentrations in the cell compartment and intercellular space is assumed. A respiration model based on Michaelis-Menten respiration kinetics without inhibition of respirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…As expected from earlier research (Bessemans et al, 2020;Delele et al, 2019), the RQ measured in the air underestimates the actual RQ value inside the pears. It is noted that this difference depends on the duration of the RQ-measurement.…”
Section: Sensitivity Of the Rq To Cool Room Operational Conditionssupporting
confidence: 79%
See 2 more Smart Citations
“…As expected from earlier research (Bessemans et al, 2020;Delele et al, 2019), the RQ measured in the air underestimates the actual RQ value inside the pears. It is noted that this difference depends on the duration of the RQ-measurement.…”
Section: Sensitivity Of the Rq To Cool Room Operational Conditionssupporting
confidence: 79%
“…A one-phase model (Eq. 2.1) was used instead of the more complex two-phase model where an equation is defined for each phase (cells and pores) individually, as Bessemans et al (2020) already showed the existence of equilibrium between the cells and pores during RQ-DCA storage conditions.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid RQ profile presented in this paper is typically a U shaped curve. The initial decrease in RQ as O2 decreases is considered to be an artefact arising from solubilisation of O2 and CO2 in apple tissues as described and modelled by Bessemans et al (2020) with RQ being underestimated due to the higher solubility of CO2 compared to O2. Comparison of the rapid RQ profile with the slow RQ profile, during which fruit can acclimatise, (Fig.…”
Section: Comparing Protocols For Rq Profilingmentioning
confidence: 99%
“…An RQ less than 1.0 occurs when lipids are used as a substrate (Cameron et al, 1994). However, Bessemans et al (2020) have produced a model to demonstrate how gradients in gas concentrations between fruit flesh and chamber headspace affect the measurement of respiration rates and the RQ. Given the high solubility of CO2 there is a tendency to underestimate RQ.…”
Section: Comparison Of Rq Profiles Between Years and Cultivarsmentioning
confidence: 99%